Kontribusi Daya Ledak Otot Tungkai Terhadap Keterampilan Smash Pada Permainan Bola Voli Di SMPN 1 Ujan Mas Kabupaten Kepahiang - Utama, Nyoman Indra; Syaputra, Roni; Masterjon, Masterjon (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to determine the contribution of leg muscle explosive power to the ability to smash volleyball at SMPN 1 Ujan Mas, Kepahiang Regency. This type of research is correlational research. The research sample is 20 people. The instrument used in this study was the Explosive Power Test of Leg Muscles Against Smash Ability. Where the results of the explosive power of the leg muscles carried out by 20 people at SMPN 1 Ujan Mas, Kepahiang Regency, had the explosive power of the leg muscles as many as 1 person (5%) had the Very Good category. As many as 6 people (30%) have a Good category. As many as 7 people (35%) have the Enough category. As many as 3 people (15%) have the Less category and as many as 3 people (15%) have the Very Less category. Then it was continued with the Smash Skills test which was attended by 20 people at SMPN 1 Ujan Mas, Kepahiang Regency. 6 people (30%) had smash skills in the Good category. As many as 7 people (35%) have the Enough category. As many as 6 people (30%) have the Less category. As many as 1 person (5%) have the Less Once category. Thus the hypothesis which reads